Re-evaluation of retested nucleic acid-positive cases in recovered COVID-19 patients: Report from a designated transfer hospital in Chongqing, China - Yan Chen; Weizhi Bai; Bin Liu; Jian Huang; Irakoze Laurent; Feng Chen; Wuquan Deng; Xiaoqiu Xiao (Elsevier, 2020)
Since the outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, Hubei Province, China [1], a large number of confirmed cases met the discharge criteria (one of which is two consecutive negative nucleic acid tests with an interval of at least 24 h) [2]. Previous studies have paid more attention to the epidemic situation of COVID-19 and patient diagnosis and treatment. Close attention also should be paid to the discharged patients. Surprisingly, a previous follow-up reported that some patients' nucleic acid retest results were positive again after discharge [3]. Factors impacting these follow-up test results should be further investigated. Since the first confirmed case was diagnosed in our hospital (Chongqing Emergency Medical Center, the designated transfer hospital) on February 4th, we confirmed a total of 17 cases. All patients infected with the novel coronavirus were transferred to a designated hospital in Southwest China's Chongqing by ambulance with an inbuilt negative-pressure chamber [4]. In the follow-up examination of these patients, RT-PCR tests were conducted again 3 days after discharged from the designated hospital. Four patients showed recurrence of positive results after a few days of discharge. Thus, we examined these cases herein, aiming to provide information for policy formulation and modification of discharge plans.